Уклонение потерпевшего от установления характера и степени тяжести вреда здоровью, причинённого преступлением: уголовно-процессуальные последствия и уголовно-правовая оценка (опыт Российской Федерации) - Клемпарский, Н. Н.; Клемпарський, М. М.; Klemparskyi, M. M. (Право і безпека. - 2015. - № 2 (57). - С. 92-97., 2015)
Представлено авторську оцінку кримінально-правової та кримінально-процесуальної дієздатності жертви злочину, пов’язаної із заподіянням шкоди здоров’ю. Встановлено, що ухилення потерпілого від експертних досліджень може перешкоджати притягненню до кримінальної відповідальності особи, яка вчинила злочин, але водночас воно знаходиться в рамках правового поля, оскільки не містить складу злочину. Висловлено пропозиції щодо покращення чинного законодавства і правозастосовної практики Російської Федерації.

Author’s assessment of the criminal and procedural, criminal legal personality of the victim of the offense of causing harm to health is presented. It is found out that the evasion of the victim from the forensic expertise (examination) may hinder bringing the guilty party to criminal liability, but it is within the legal boundaries, since it does not contain features of corpus delicti. It is noted that the impact of the victim to the process of solving criminal and conflict situation essentially requires not only the procedural, but also an independent criminal and legal evaluation. This problem is closely related to the definition of criminal legal personality of other participants of criminal and legal relations than the offender. It was concluded that, despite the fact that evasion of the victim from the assessment of the nature and degree of severity of the harm to health considerably complicates the establishment of grounds for initiation of a criminal case, prevents obtaining necessary evidence against a suspect or accused, such a behavior from the perspective of the Criminal Code of Russian Federation is valid and is not prohibited under the threat of punishment or using any other measures of criminal liability. In this context, it is quite reasonable to consider the issue of the criminalization of the evasion of the victim to participate in the investigation, and moreover to obstruct the justice and preliminary investigation, first of all, in serious and very serious crimes. The refusal of the victim of the right to prosecute a perpetrator is completed with the disinterest of law enforcement agencies to initiate and investigate criminal cases. Nowadays, this has led to the formation of a sort of tradition within law enforcement practice, which is expressed in the form of legitimate refusal to initiate criminal cases. This practice should be considered illegal. The mean that can be used to overcome this tradition should be prosecutor’s abolition of the decision about refusal to initiate criminal case or its termination because of such circumstances.

Представлено авторську оцінку кримінально-правової та кримінально-процесуальної дієздатності жертви злочину, пов’язаної із заподіянням шкоди здоров’ю. Встановлено, що ухилення потерпілого від експертних досліджень може перешкоджати притягненню до кримінальної відповідальності особи, яка вчинила злочин, але водночас воно знаходиться в рамках правового поля, оскільки не містить складу злочину. Висловлено пропозиції щодо покращення чинного законодавства і правозастосовної практики Російської Федерації.
Klemparskyi, M.M. (2015), “Evasion of the victim from establishing the nature and degree of severity of the harm to health caused by a crime: criminal and procedural consequences and criminal and legal assessment (experience of Russian Federation)” [“Uklonenie poterpevshego ot ustanovlenija haraktera i stepeni tjazhesti vreda zdorov’ju, prichinjonnogo prestupleniem: ugolovno-processual’nye posledstvija i ugolovno-pravovaja ocenka (opyt Rossijskoj Federacii)”], Pravo i Bezpeka, No. 2, pp. 92–97.
Клемпарский, Н. Н. Уклонение потерпевшего от установления характера и степени тяжести вреда здоровью, причинённого преступлением: уголовно-процессуальные последствия и уголовно-правовая оценка (опыт Российской Федерации) // Право і безпека. - 2015. - № 2 (57). - С. 92-97.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Росія; потерпілий; заподіяння шкоди здоров’ю; реституція; судово-медична експертиза; відсутність складу злочину; victim; harm to health; restitution; forensic expertise; absence of corpus delicti; потерпевший; причинение вреда здоровью; реституция; судебно-медицинская экспертиза; отсутствие состава преступления; Russia; Российская Федерация